DEVELOPING ENGLISH SUPPLEMENTARY BOOK FOR TENTH GRADE ONLINE BUSINESS AND MARKETING STUDENTS - Muhammad Hasan Fahmi Ilma; Istina Atul Makrifah; Tyas Alhim Mubarok (PROJECT (Professional Journal of English Education), 2023)
English material in Islamic Vocational High School of Kanigoro Blitar majoring in online business and marketing still using general English and not specified by the major itself. This study has been conducted to find out how and the result of the development of English supplementary book for online business and marketing class. The research and development process of this article is using ADDIE model which had been developed by Dick and Carry and it has five phases (1) Analysis, (2) Design, (3) Develop, (4) Implementation, (5) Evaluation. The researcher also took quantitative data for reliability and validity test by giving questionnaire in order to know how unique, valid, and appropriate media with the material. The questionnaire will be used as a evaluation consideration and if needed the product will be revised based on the data that has been gained. The questionnaire to test students’ satisfaction got 88% score which is defined as excellent, based on the questionnaire, students feel highly satisfied on the media design where the cover has 4.57 point out of 5 and font, illustration, color pick, and layout scored 4.78 out of 5.